The impact of automatic speech recognition technology on second language pronunciation and speaking skills of EFL learners: a mixed methods investigation - Sun, Weina (Frontiers in Psychology, 2023)
This study used an explanatory sequential design to investigate the effectiveness of automatic speech recognition technology (ASR) with peer correction in enhancing second language (L2) pronunciation and speaking performance of English as a Foreign Language (EFL) learners. A total of 61 intermediate-level Chinese EFL learners were randomly assigned to either a control group (CG) receiving traditional teacher-led feedback and instruction or an experimental group (EG) using ASR technology with peer correction. Read-aloud tasks, spontaneous conversations, and IELTS speaking tests were used to collect data for L2 pronunciation and speaking skill. Also, semistructured interviews were carried out with a number of the participants to explore their perceptions of the ASR technology. The quantitative results showed that the EG outperformed the CG in all measures of L2 pronunciation, including accentedness and comprehensibility. Additionally, the EG demonstrated significant greater improvements in global speaking skill. The qualitative analysis of the interviews revealed that the majority of the participants found the ASR technology helpful in improving their L2 pronunciation and speaking skills. Overall, the findings suggest that ASR technology with peer correction can be an effective tool in enhancing L2 pronunciation and speaking skills in EFL learners.